Intelligent Computer Systems of New Generation and Complex Technology of Their Development, Application and Modernization - V. V. Golenkov; N. A. Gulyakina; V. P. Ivashenko; D. V. Shunkevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper considers the trends in the development of artiﬁcial intelligence technologies in BSUIR for the last ﬁve years, lists the main results obtained during this period both in the ﬁeld of development of artiﬁcial intelligence technologies themselves, and in the ﬁeld of education in artiﬁcial intelligence and realization of interaction between teams of specialists working in this ﬁeld. The necessity of transition to new-generation intelligent computer systems with a high level of interoperability and creation of an appropriate complex technology for their development, maintenance and operation is substantiated. The problems hindering the active development and implementation of new generation intelligent computer systems are considered. The concept of semantic space as a basis for representation and integration of knowledge in intelligent computer systems of new generation is considered. The principles of implementation of hardware platform for interpretation of information processes in the semantic space – associative semantic computer – are considered.